ARTISTICALLY SIGNIFICANT RELIGIOUS CONCEPTS IN THE NOVEL BY M.A. SHOLOKHOV “AND QUIET FLOWS ON DON” (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-3-52-61The article is devoted to the analysis of the role of the most frequent concepts of the semantic field of religion in the author’s implementation of artistic tasks. It has been revealed that within the framework of an artistic text, not only individual author’s concepts arise that accumulate the imagery of the work, but also general cultural concepts expand their content and acquire new meanings due to the general metaphorical nature of the artistic text. But the specificity of a literary text, in our opinion, lies in the fact that almost any lexeme can acquire conceptual meaning as part of the author’s conceptual sphere. The conceptual sphere of the novel is unusually rich. The article analyzes a small set of lexemes that verbalize the main concept of the thematic group religion from the point of view of their semantics and contextual meanings. Sholokhov showed quite accurately that religion in the life of aCossack has, rather, an everyday character: observance of familiar formulas, rituals, holidays has little correlation with truly Christian behavior, however, the most lexemes that implement the concept of religion are faith, church, bell tower, bell ringing – play a huge role both in the characterization and attitude of the characters and in the development of the plot, serving as unique markers of the changing artistic picture of the world in the novel.Key words: Sholokhov, “And Quiet Flows on Don”, concept, faith, artistic picture of the world